2022
DOI: 10.1002/ajh.26629
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and clinical efficacy of anti‐SARS‐CoV‐2 vaccination in patients with hematological malignancies: Results of a prospective cohort study of 365 patients

Abstract: Since its outbreak, Covid-19 has been responsible for more than 6 000 000 deaths. 1 Cancer is one of the most important risk factors for severe disease and death; hematological malignancies (HMs), specifically, have been associated with an estimated mortality rate of 37%. 2At present, the anti-SARS-CoV-2 vaccination represents the most effective strategy to reduce the incidence and severity of Covid-19.Here, we present the results of a prospective, cohort study aimed to evaluate the humoral and cell-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 2 publications
3
26
3
Order By: Relevance
“…The authors showed an overall incidence of breakthrough infections of 2.98 per 10000 person-days, significantly lower in post-vaccine seropositive patients, whereas a clear correlation between T-cellular immunity response and risk of post-vaccine infection has not been found. 33 In our study, we reported an overall 30-day-mortality rate of 9.2%, mainly driven by COVID-19 infection as a direct or contributing factor which is significantly lower than in the pre-vaccination era. [1][2][3][4] Moreover, the 30-days mortality rate in symptomatic patients only was of 10.3%.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The authors showed an overall incidence of breakthrough infections of 2.98 per 10000 person-days, significantly lower in post-vaccine seropositive patients, whereas a clear correlation between T-cellular immunity response and risk of post-vaccine infection has not been found. 33 In our study, we reported an overall 30-day-mortality rate of 9.2%, mainly driven by COVID-19 infection as a direct or contributing factor which is significantly lower than in the pre-vaccination era. [1][2][3][4] Moreover, the 30-days mortality rate in symptomatic patients only was of 10.3%.…”
Section: Discussionmentioning
confidence: 71%
“…This lack of direct correlation between serological response and survival might be at least in part explained by the putative role of anti-SARS-CoV-2 induced cellular immunity, as suggested by several studies, [23][24]40 since the presence of memory T-cells might control the infection and prevent severe COVID-19 even if high titers of long-lasting neutralizing antibodies are not elicited. 41 However, since a recently published study did not find a clear correlation between post-vaccine T-cell immunity and vaccine clinical efficacy, 33 further studies are warrant to better understand this aspect. Another possible explanation is related to the role of the specific anti-SARS-CoV-2 treatments (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies in cancer patients suggests that those who did not achieve seroconversion after complete vaccination may benefit from an additional dose of vaccine. 34 , 57 , 58 A study involving 88 vaccinated cancer patients, showed that 56% of the 32 patients who were seronegative (mostly patients with hematologic malignancies) achieved seroconversion after booster vaccination. 57 CAPTURE is a prospective cohort study investigating vaccine response in patients with cancer after two doses of either the BNT162b2 or ChAdOx1vaccine, and after a third vaccination (booster) with BNT162b2.…”
Section: Immunization Of Lymphoma Patients Against Sars‐cov‐2mentioning
confidence: 99%
“…In addition, programs of booster vaccinations need to be implemented as the emerging data on additional vaccine doses in patients with no seroconversion after the first vaccination cycle are promising. 34 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation